The implementation of circular economy concept in the Polish coal combustion products sector: Selected problems - Janusz Rosiek (Economic and Environmental Studies (E&ES), 2018)
The EU economy is currently losing a significant amount of potential secondary raw materials which are present in waste streams (particular numerical data are presented in the paper). In the total amount of generated waste, the share of Coal Combustion Products (CCPs) and Coal Mining Products (CMPs) is particularly high, which is generated mainly by Central and Eastern European Countries (CEECs), where we come to deal with high consumption of energy produced by coal combustion and coal mining processes. The problem concerns, in particular, the Polish economy. Consequently, the European Commission (EC) has developed a closed-loop (circular) economy concept (CEC), whose implementation should contribute to reducing CCPs negative impact on the economy, not only in the ecological, but also in social and economic aspects. Closed-loop (circular) economy keeps products, parts and materials in economic circulation, as long as possible, using as little resources as possible. This concept was presented in the document published by the European Commission: Circular Economy Package, which also includes the Communication of the Commission: Closing the Loop - An EU Action Plan for the Circular Economy (2015). Recent trends suggest that further progress in resource efficiency is possible and it can bring major economic, environmental and social benefits. Turning waste, especially CCPs, into a resource is an essential part of increasing resource efficiency and closing the loop in a circular economy. There are four key areas of CCPs use: construction, road construction, energy and road maintenance. Increasing the use of CCPs can be achieved by granting a legal status to waste products and convincing consumers and business of the following benefits of using them: decreasing production costs by substituting natural aggregate with waste aggregates (based on CCPs), reducing greenhouse gas emissions, and increasing energy efficiency. As a result, CCPs must comply with certain technical standards set by the EU and implemented in the Polish economy. The study attempts to estimate, using comparative analysis, the economic, social and environmental benefits of implementation of CEC in the CCPs sector of the Polish economy.
Keywords: Q31; Q32; Q53; 330; Circular Economy Concept (CEC) implementation; Coal Combustion Products (CCPs); the EU and the Polish economies